Role of Nutrition Education in Pharmacy Curriculum-Students' Perspectives and Attitudes - Majid Mufaqam Syed-Abdul; Syed Sadath Kabir; Dhwani Satishkumar Soni; Tony J. Faber; Jeremy T. Barnes; Maureen T. Timlin (MDPI AG, 2021)
Many pharmacists report they lack nutritional knowledge and believe the best time to educate pharmacists about nutrition is during pharmacy school. Purpose: This study was conducted to determine if today's pharmacy students receive education in nutrition and if they realize the importance of a nutrition course. Methods: Ninety-five pharmacy students attending pharmacy school were surveyed in two pharmacy schools in the United States. Results: The survey showed only 13.7% received nutrition education and 82.9% of students believed nutrition education should be incorporated into the pharmacy degree curriculum. When the pharmacy-related experience was taken into account, 73.3% of students believed that a nutrition course should be incorporated into the curriculum. Conclusion: This study suggests that pharmacy students from two major universities in Alabama and Illinois realize the importance of nutrition education and believe a nutrition course should be incorporated into the pharmacy degree curriculum.